Application of Deep Eutectic Solvents (DES) for the Synthesis of Iron Heterogeneous Catalyst: Application to Sulfamethoxazole Degradation by Advanced Oxidation Processes - Puga, Antón; Rosales, Emilio; Pazos, Marta; Sanromán, María Angeles (Catalysts, 2023)
The development of novel approaches to the remotion of pharmaceuticals in wastewater is a subject of concern due to their effect on living beings and the environment. Advanced oxidation processes and the use of relevant catalysts are feasible treatment alternatives that require further development. The development of suitable heterogeneous catalysts is a necessity. This work proposes the synthesis of an iron catalyst in a deep eutectic solvent (Fe-DES) composed of choline chloride and citric acid, which was physically and chemically characterized using SEM-EDS and TEM, FTIR, RAMAN, XRD and XPS. The characterisation confirmed the presence of iron in the form of hematite. Fe-DES was shown to be a multipurpose catalyst that can be applied in the removal of sulfamethoxazole as a reagent in the Fenton and electro-Fenton processes and as an activator of peroxymonosulfate (PMS) processes. After testing the catalyst with the aforementioned techniques, the best result was achieved by combining these processes in an electro-PMS, with great efficiency achieved by dual activation of the PMS with the catalyst and electric field, attaining total elimination at natural pH in 90 min. Furthermore, the degradation was confirmed by the detection of short-chain carboxylic acids (oxalic, succinic, and acetic) and reduction in toxicity values. These results confirm the suitability of Fe-DES to degrade high-priority pharmaceutical compounds.